Proceedings of the 2005 Particle Accelerator Conference
DOI: 10.1109/pac.2005.1591085
|View full text |Cite
|
Sign up to set email alerts
|

Beam Energy Scaling of Ion-Induced Electron Yield From K+ Ions Impact on Stainless Steel Surfaces

Abstract: The cost of accelerators for heavy-ion inertial fusion energy (HIF) can be reduced by using the smallest possible clearance between the beam and the wall from the beamline. This increases beam loss to the walls, generating ion-induced electrons that could be trapped by beam space charge potential into an "electron cloud", which can cause degradation or loss of the ion beam. In order to test the physical mechanism model of ioninduced electrons production we have measured the impact of K+ ions with energies up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…4. We found that emission scaled with the electronic component of ion stopping in stainless steel, dE/dx [14], as has been found previously at higher energies [15]. However, the emission varied more slowly with the ion angle of incidence than 1/cos(θ), unlike measurements with 1 MeV K+ [12] and higher energy ions [13].…”
Section: B Additional Experimental Tools and Applicationssupporting
confidence: 81%
See 1 more Smart Citation
“…4. We found that emission scaled with the electronic component of ion stopping in stainless steel, dE/dx [14], as has been found previously at higher energies [15]. However, the emission varied more slowly with the ion angle of incidence than 1/cos(θ), unlike measurements with 1 MeV K+ [12] and higher energy ions [13].…”
Section: B Additional Experimental Tools and Applicationssupporting
confidence: 81%
“…However, the emission varied more slowly with the ion angle of incidence than 1/cos(θ), unlike measurements with 1 MeV K+ [12] and higher energy ions [13]. Based on a modified Sternglass model [16], we have modeled the dependence on ion energy and the ion angle of incidence [14], evaluating a dE/dx model with the SRIM code [20]. The modelled electron yield in Fig.…”
Section: B Additional Experimental Tools and Applicationsmentioning
confidence: 99%
“…Electron emission decreases by factors ~20 from grazing to normal incidence, whereas desorption scales as a fractional power of 1/cos, decreasing by factors 2-3 over the same range of angles [27,28]. Both electron emission and gas desorption are minimized for impact near 0°, i.e., normal incidence and scale with the electronic component of ion energy loss in matter dE e /dx [2,3]. Gas will cause charge exchange (K + → K 0 ) and ionization (K + → K ++ or higher ionization states); ions that change charge will hit the beam tube in a long accelerator.…”
Section: Issuementioning
confidence: 99%
“…2. Measured and modeled the scaling of electron emission with the electronic component of ion energy loss in matter [2]. 3.…”
Section: Introductionmentioning
confidence: 99%